The Evolution of Endogenous Viral Elements - Holmes, Edward C. (Cell host & microbe, 2011)
Endogenous retroviruses are a common component of the eukaryotic genome, and their evolution and potential function have attracted considerable interest. More surprising was the recent discovery that eukaryotic genomes contain sequences from RNA viruses that have no DNA stage in their life cycle. Similarly, several single-stranded DNA viruses have left integrated copies in their host genomes. This review explores some major evolutionary aspects arising from the discovery of these endogenous viral elements (EVEs). In particular, the reasons for the bias toward EVEs derived from negative-sense RNA viruses are considered, as well as what they tell us about the long-term “arms races” between hosts and viruses, characterized by episodes of selection and counter-selection. Most dramatically, the presence of orthologous EVEs in divergent hosts demonstrates that some viral families have ancestries dating back almost 100 million years, and hence are far older than expected from the phylogenetic analysis of their exogenous relatives.